Social participation of people with disabilities in organized community sport. A systematic review - Klenk, C.; Albrecht, J.; Nagel, S. (German Journal of Exercise and Sport Research, 2019)
Sport is considered to have a high potential with respect to social participation of people with disabilities, in particular in inclusive settings. However, people with disabilities continue to face social exclusion in sport, as they are underrepresented in organized mainstream sport activities and disability sport often remains separate. Thus, organized community sport can both support and foster but also restrict or even impede social participation of people with disabilities resulting in that the organized sport`s contribution to social participation is also critically questioned. This article provides a systematic review of current research on social participation of people with disabilities in organized community sport in separated and inclusive settings. The review of 25 relevant studies revealed four topics based on Koster and colleagues` applied theoretical framework that are associated with social participation in organized community sport: (1) social contacts, interactions and friendships, (2) identity, self-perception and acceptance, (3) social support and (4) community integration. The results draw a rather ambivalent picture of social participation of people with disabilities in organized community sport. However, most of the studies showed positive social benefits to people with disabilities for both separated and inclusive setting with respect to the four topics that underscore the potential of organized sport. However, there are also studies reporting negative aspects people with disabilities experienced, in particular when participating in inclusive settings. This article concludes by pointing to capacity building of disability and mainstream community sport organizations in order to strengthen the positive effects while minimizing and mitigating the negative effects to ensure effective social participation of people with disabilities. Sport wird ein hohes Potenzial bezüglich der sozialen Partizipation von Menschen mit Behinderungen zugesprochen, insbesondere unter inklusiven Rahmenbedingungen. Jedoch erfahren Menschen mit Behinderung beim Sport soziale Ausgrenzung: Sie sind bei Aktivitäten des organisierten Nicht-Behindertensports unterrepräsentiert, der Behindertensport findet zudem oftmals separativ statt. Folglich kann der organisierte Sport die soziale Partizipation von Menschen mit Behinderungen unterstützen und fördern, aber auch beschränken. Daher wird der Beitrag des organisierten Sports zur sozialen Partizipation auch kritisch hinterfragt. Der vorliegende Beitrag bietet eine systematische Übersicht aktueller Studien zur sozialen Partizipation von Menschen mit Behinderungen im organisierten separativen und inklusiven Sport. Basierend auf dem theoretischen Konzept von Koster et al. zeigt die Übersicht von 25 relevanten Studien vier Themen auf, die mit sozialer Partizipation im organisierten Sport assoziiert sind: 1. soziale Kontakte, Interaktionen und Freundschaften, 2. Identität, Selbstwahrnehmung und Akzeptanz, 3. soziale Unterstützung sowie 4. Integration in die Gemeinschaft. Die Ergebnisse zeichnen ein ambivalentes Bild: Einerseits zeigt die Mehrzahl der Studien den positiven Beitrag sowohl des separativen als auch des inklusiven Sports in Bezug auf die vier Themen auf, was damit das Potenzial des organisierten Sports bezüglich sozialer Partizipation unterstreicht. Andererseits fanden sich aber auch Studien, die negative Erfahrungen für Menschen mit Behinderung dokumentieren, insbesondere unter inklusiven Bedingungen. Der Beitrag schließt mit einem Verweis auf den Kapazitätenaufbau für Sportorganisationen mit dem Zweck, die positiven Effekte zu stärken und zugleich die negativen Effekte zu minimieren, um so eine wirksame soziale Partizipation von Menschen mit Behinderung zu gewährleisten.